Anti-endotoxic activity and structural basis for human MD-2·TLR4 antagonism of tetraacylated lipid A mimetics based on βGlcN(1↔1)αGlcN scaffold. Issue 5 (July 2015) - Garate, Jose Antonio; Stöckl, Johannes; del Carmen Fernández-Alonso, María; Artner, Daniel; Haegman, Mira; Oostenbrink, Chris; Jiménez-Barbero, Jesús; Beyaert, Rudi; Heine, Holger; Kosma, Paul; Zamyatina, Alla
Interfering with LPS binding by the co-receptor protein myeloid differentiation factor 2 (MD-2) represents a useful approach for down-regulation of MD-2·TLR4-mediated innate immune signaling, which is implicated in the pathogenesis of a variety of human diseases, including sepsis syndrome. The antagonistic activity of a series of novel synthetic tetraacylated bis-phosphorylated glycolipids based on the βGlcN(1↔1)αGlcN scaffold was assessed in human monocytic macrophage-like cell line THP-1, dendritic cells and human epithelial cells. Two compounds were shown to inhibit efficiently the LPS-induced inflammatory signaling by down-regulation of the expression of TNF-α, IL-6, IL-8, IL-10 and IL-12 to background levels. The binding of the tetraacylated by ( R )-3-hydroxy-fatty acids (2 × C12, 2 × C14 ), 4, 4′-bisphosphorylated βGlcN(1↔1)αGlcN-based lipid A mimetic DA193 to human MD-2 was calculated to be 20-fold stronger than that of Escherichia coli lipid A. Potent antagonistic activity was related to a specific molecular shape induced by the β, α(1↔1)-diglucosamine backbone. 'Co-planar' relative arrangement of the GlcN rings was inflicted by the double exo -anomeric conformation around both glycosidic torsions in the rigid β, α(1↔1) linkage, which was ascertained using NOESY NMR experiments and confirmed by molecular dynamics simulation. In contrast to the native lipid A ligands, the binding affinity of βGlcN(1↔1)αGlcN-based lipid A mimetics to human MD-2 was independent on the orientation of the diglucosamine backbone of the synthetic antagonist within the binding pocket of hMD-2 (rotation by 180°) allowing for two equally efficient binding modes as shown by molecular dynamics simulation.